Association between a specific monocyte subset and heart failure with preserved ejection fraction in patients with uremia - Xinrui Wang; Minghui Song; Lu Ma; Yang Yang (Exploration of Cardiology, 2025)
Aim: This study aimed to establish a model based on gene expression in peripheral blood mononuclear cells (PBMCs) for predicting the incidence of heart failure with preserved ejection fraction (HFpEF) in patients with end-stage renal disease (ESRD). Methods: PBMCs were isolated from patients with stage 2–3 chronic kidney disease, ESRD, ESRD with HFpEF, and ESRD with heart failure with reduced ejection fraction (HFrEF). Differences in the expression of differentially expressed genes in PBMCs among different groups were compared using microarray. Results: In total, 43 differentially expressed genes were specifically identified in patients with ESRD with HFpEF. The expression of four genes encoding MMP7, S100A8, CXCR3, and CD163 was significantly upregulated. Hence, it played a role in the development of HFpEF. Based on these findings, a nomogram was established using data from the database including 343 patients with ESRD. The receiver operating characteristic curve, calibration curve, model consistency index, and decision curve analyses showed that the nomogram had a good predictive performance for predicting HFpEF. Conclusions: Specific gene detections can be an important early warning indicator and guide physicians in evaluating the risk of HFpEF in ESRD.